Diagnostic Study on Brucella melitensis isolated from Human in Wassit province - Basil A. Abbas; Haethem Q. Mohammed; Jalal A. Tofah (College of Pharmacy / Mustansiriyah University, 2012)
This study was performed to identify the extent of the infection with Brucellosis caused by Brucella melitensis in humans in Kut city through a period of nine months from September 2007 till May 2008. One hundred blood samples were collected from humans and all were suspected in having brucellosis while twenty blood samples were collected from humans and all were known in not being suspected in having brucellosis and has no history in having such disease according to the performed serological tests (Rose Bengal test and 2-Mercaptoethanol test). The recorded cases for the brucellosis suspected samples were 58 Cases (58%) that positive for Rose Bengal test which the acute phases. With the use of 2-Mercaptoethanol test, the results showed that the chronic phase positive cases reached up to 12 samples (20.68%). Blood sample from the infected cases used for the purpose of bacterial isolation. Later by using Castaneda biphase medium the results showed that out of 58, 8 (13.79%) isolates were positive for the test. This method has been characterized by its time shortness for isolation. A number of morphological and biochemical tests had been carried including the direct examination, Catalase, Oxidase , Urease, IMVIC test, inoculation into nitrate reduction test medium and the ability to grow in the bacteriostatic dyes medium under the presence of basic fuchsin dye with two concentrations 1:50000 and 1:100000. The results of the biotyping of isolates showed that 2 isolates out of 8 isolates (25%) were agglutinated with monospecific antisera for Brucella abortus (A) so it was belonging to the biotype 2. While the rest 6 isolates (75%) which were agglutinated simultaneously with monospacific antisera for Brucella abortus (A) and with monospecific antisera for Brucella melitensis (M) so it was belonging to the biotype 3. All isolate's colonies which were isolated from the infected cases were in the smooth phase and showed its negativity to the virulence factors tests represented by the enzymes of (hemolysin, gelatin hydrolysis, lecithinase, DNAase). All isolates were subjected to the antibiotics sensitivity test toward twenty two antibiotics and they were sensitive in a rate of 100% toward Streptomycin, Pipracillin, Norfloxacin, Ciprofloxacin, Rifampicin, Doxycyclin and Cephoxitin while toward Chloramphenicol it was 92% and for Tetracycline and Gentamycin it was 80% for both. At the same time the isolates were resistant at a rate 100% to Augmentin, Ceftriaxone, Amoxicillin, Nalidixic acid, Lincomycin, Cefixine, Cloxacillin, Clindamycin, and the mixed Trimethoprin and Sulfamethoxazole